Rural Isolation: The Need for Information - S. L. Ward (Educational Considerations, 1986)
Adults faced with a crisis need immediate access to information more than entry into longer-term educational programs. This article describes one state's attempts to coordinate its educational resources in response to the agricultural crisis.